Pengaruh Pelayanan Prima, Ketanggapan Dan Komunikasi Terhadap Kepuasan Nasabah PT. Rifan Financindo Berjangka - Amanda, Annisa Risty; Ginting, Kristi Endah Ndilosa; Surbakti, Daniel; Yunita, Mella (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research was conducted at the Bojonegoro Regency Regional Finance and Asset Management Agency. This research has the aim of assessing employee performance where this study is specifically focused on the influence of leadership style, work commitment and work environment with a population of all employees at the Bojonegoro Regency Regional Financial and Asset Management Agency totaling 60 samples, using a 21-question Likert scale survey to test the research hypothesis through the SPSS program. The findings in the study concluded that if the leadership style is qualified or high, employee performance will increase, which means that leadership style has a positive and significant effect on employee performance variables. Based on the results of multiple linear regression analysis, commitment affects employee performance or has a positive effect and the work environment has a positive effect on performance. Limitations This research focuses on the Bojonegoro Regency Regional Financial and Asset Management Agency in East Java Province, East Java Province.